Synthesis of Graphene Oxide using Hummers Method as Adsorbent of Malachite Green Dye - Amri Amri; Yulizah Hanifah (Indonesian Journal of Material Research, 2023)
Graphene oxide materials were successfully synthesized using the Hummer method with XRD, FTIR, and BET characterization results. Graphene oxide material was used as malachite green dye adsorbent. The surface area of graphene oxide material and the maximum adsorption capacity were 157.360 m2/g and 106.383 mg/g. The selectivity process of graphene oxide material to the three dyes showed the most effective malachite green dye. The optimum pH of adsorption was obtained at pH 4. The optimum time of adsorption occurred at 120 minutes and the kinetics model followed PSO. The isotherm data followed Langmuir isotherm and the adsorption process was endoetrmic and spontaneous. The regeneration results showed the ability up to five cycles with a decrease of 40.019% from 96.698% to 56.679%.